penelitian pemanfaatan minarex sebagai softener untuk pembuatan rol karet gilingan padi - Buchori, A.; Sumasto, Yuwono (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1994)
The objective of the research is to use minarex (new product from PERTAMINA) as a softener for making rice mill roller compound. The formula of the compound applied four kinds of minarex, namely A, B, C and D minarex, type 2 and 3 each, by varying minarex : 3, 4, and 5 parts. The mastication and mixing process used two roll mill machine and the compound was vulcanized at 150oC the pressure 150 Kg/Cm2 and 9 minute curing time. Then it should be tested their_physical properties : tensile strength, elongation at break, abrasion resistance, hardness before and after aging. The result of the test statistically prove that all minarex for 5 parts is the best physical properties and fulfilled the specificatioh, of SII 1902 - 86